Realization of LTE physical layer baseband processing architecture for narrowband IOT - Syed Ameer Abbas, S; Venisubha, M; Siva Gayathri, S; J. Thiruvengadam, S (International Journal of Engineering and Technology, 2018)
The 3GPP Long Term Evolution represents the major innovation in cellular technology. NB-IoT is the 3GPP standard for machine to machine communication finalized within LTE Release13. NB-IoT technology occupies frequency band of 180 kHz bandwidth which corresponds to one resource block in LTE transmission. The Long Term Evolution (LTE) supports higher data rates, higher bandwidth, Low latency, good Quality of Service whereas objective of Narrow Band Internet of Things (NB - IOT) is to achieve extended coverage, to support massive number of smart devices and have multi - year long battery life. So the main focus is linking LTE with IOT. The objective of this paper proposes transmitter architecture of PUCCH (Physical Uplink Control Channel) and PUSCH(Physical uplink Shared Channel) in SISO and SIMO configurations for physical uplink channels of LTE. The physical uplinkÂ and downlink channel processing involves scrambling, modulation, layer mapping, transform precoding, and resource element mapping at the transmitter and the receiver block to have demapping from the resource elements and detection of data. At present, the data for on-off control has been worked and the whole framework has been simulated using Modelsim and implemented in Spartan 6.